Detection of hepatitis B virus pre-S1 and pre-S2 determinants in paraffin wax embedded liver tissue: importance of reagents used. Issue 7 (July 1991) - Hadzic, N; Alberti, A; Portmann, B; Vergani, D
Abstract : The presence of pre-S polypeptides in paraffin wax embedded liver sections from the biopsy specimens of 15 hepatitis B surface antigen (HBsAg) seropositive patients (five with chronic persistent hepatitis (CPH), four with chronic active hepatitis (CAH), four with cirrhosis and two "healthy" HBsAg carriers) was investigated using monoclonal antibodies directed to distinct epitopes on pre-S1 (18/7 and TO 606) and pre-S2 (5535 and Q 19/10). Pre-S1 was found in 13 cases when MA 18/7 was used but in only one specimen when TO 606 was used. Pre-S2 was detected in all the biopsy specimens with 5535 and in eight samples with Q 19/10. Mild enzymatic digestion annulled the staining of all monoclonal antibodies but Q 19/10. No association was observed between pre-S polypeptide expression and hepatitis B virus (HBV) replication or disease severity. Pre-S polypeptides can be detected readily in paraffin wax embedded material but the results obtained largely depend on the monoclonal antibodies used.